Systems Approach in the Study of the Attrifcutes of the Universe of Subjects - Neelameghan, A. (Journal of Information and Knowledge, 1972)
Study of the structure, modes of formation, and patterns of development of the universe of subjects and its components, and the establishment of methodologies for such a study, are pre-requisites for the formulation of guidelines for the design and development of document finding systems. In studying the attributes of the universe of subjects and of its components it is helpful to consider a subject as a system. The general systems approach can be helpfully applied to the study of the attributes of the universe of subjects. These points are discussed with illustrative examples.